Iron corrosion concomitant with nitrate reduction by Iodidimonas nitroreducens sp. nov. isolated from iodide-rich brine associated with natural gas - Iino, Takao; Oshima, Kenshiro; Hattori, Masahira; Ohkuma, Moriya; Amachi, Seigo (Frontiers in Microbiology, 2023)
Microbially influenced corrosion (MIC) may contribute significantly to corrosion-related failures in injection wells and iron pipes of iodine production facilities. In this study, the iron (Fe 0 ) corroding activity of strain Q-1 isolated from iodide-rich brine in Japan and two Iodidimonas strains phylogenetically related to strain Q-1 were investigated under various culture conditions. Under aerobic conditions, the Fe 0 foil in the culture of strain Q-1 was oxidized in the presence of nitrate and yeast extract, while those of two Iodidimonas strains were not. The amount of oxidized iron in this culture was six times higher than in the aseptic control. Oxidation of Fe 0 in aerobic cultures of nitrate-reducing bacterium Q-1 was dependent on the formation of nitrite from nitrate. This Fe 0 corrosion by nitrate-reducing bacterium Q-1 started after initial nitrite accumulation by day 4.Nitrate reduction in strain Q-1 is a unique feature that distinguishes it from two known species of Iodidimonas. Nitrite accumulation was supported by the encoding of genes for nitrate reductase and the missing of genes for nitrite reduction to ammonia or nitrogen gas in its genome sequence. Phylogenetic position of strain Q-1 based on the 16S rRNA gene sequence was with less than 96.1% sequence similarity to two known Iodidimonas species, and digital DNA-DNA hybridization (dDDH) values of 17.2%−19.3%, and average nucleotide identity (ANI) values of 73.4%−73.7% distinguished strain Q-1 from two known species. In addition of nitrate reduction, the ability to hydrolyze aesculin and gelatin hydrolysis and cellular fatty acid profiles also distinguished strain Q-1 from two known species. Consequently, a new species, named Iodidimonas nitroreducens sp. nov., is proposed for the nitrate-reducing bacterium strain Q-1 T . * The summed feature represents a mixture of fatty acids that cannot be separated by the MIDI system. Summed feature 3 contained C16:1ω7c, and/or C16:1ω6c. Summed feature 8 contained C18:1ω7c.